LITERATUR REVIEW PENGARUH PEMBERIAN MULTI MODAL ANALGESIA INTRA ANESTESI TERHADAP STABILITAS TEKNANAN DARAH PASIEN SELAMA OPERASI - Fahria Nur Maulida; Miftahul Khoeriyah; Nidaul Khaira (Jurnal Riset Multidisiplin Edukasi, 2025)
Blood pressure stability during surgery is crucial to prevent anesthetic complications. Blood pressure fluctuations often occur due to pain response and surgical stress. One effective way to control this condition is through intra-anesthetic multimodal analgesia, which involves the use of a combination of analgesic drugs with different mechanisms of action. Research by (Wang et al. 2025),  (Negm et al. 2025) (Besnier et al. 2024) shows that a combination of drugs such as dexmedetomidine, lidocaine, and magnesium sulfate can maintain hemodynamic stability and reduce the need for inhalation anesthesia. Therefore, it is important to review the scientific evidence regarding the effect of multimodal intra-anesthetic analgesia on blood pressure stability in patients during surgery. Objective: This literature review aims to determine and analyze the effect of multimodal intra-anesthetic analgesia on blood pressure stability in patients during surgery, based on the results of relevant national and international studies in the last five years (2023–2025). Research Method: This study design uses a literature review method, examining and analyzing 10 scientific journals focusing on the topic of multimodal intra-anesthetic analgesia. The journals used consist of six national journals and four international journals from reliable sources such as the Indonesian Journal of Anesthesiology Nursing and BMC Anesthesiology. The analysis was conducted by reviewing the research design, interventions used, blood pressure parameters, and intraoperative hemodynamic stability results. Research Results: The results of the review show that multimodal intra-anesthetic analgesia is effective in maintaining blood pressure stability during surgery. The combination of drugs such as dexmedetomidine, lidocaine, paracetamol, low-dose ketamine, and magnesium sulfate was able to reduce blood pressure fluctuations and the need for inhalation anesthesia compared to the use of opioids alone. All journals reviewed showed consistent results supporting the positive effects of this approach on patient hemodynamic stability.